The Relationship Between the Duration of Breast Feeding and Child Weight Gain up to the End of the Age of 24- Months - Allahgholi L. PhD Student; Rahmani A. PhD Student; ES Hajikazemi; Hosseini AF. MSc (Iran University of Medical Sciences, 2011)
Background & Aim: Breast feeding is the most important and decisive factor in Children's state of health and nutrition, especially in societies with lower socio-economic status. Beastfeeding plays an important role in child health and development. Acordingly this study was carried out with the aim of determining the ralationship between breastfeeding and child weigth gain up to the end of 24 months of age.   Material & Methods: It was a correlational predictive study. The sample consisted of 307 mothers of 2-3 years old children who have been visited for monitoring their children's growth in heath canters of west of Tehran. They were recruited by stratified sampling method. Mothers & children's data was collected by questionnaire & analyzed using SPSS-PC-(v.10).   Results: pearson correlation test indicated that there is no significant relationship between breastfeeding duration & children's weight in 6 and 12 months of age. However, there was a converse significant relationship between breastfeeding duration and the children's weight in 24 months of age (p=0.003). There was also a significant relationship between the children's sex and their weight in 6, 12 and 24 months of age (p=0.000). No significant association was found between children's weight in 6, 12 and 24 months of age and mothers' age, number of deliveries, mothers' level of education and job status, participation in educational courses for breast feeding, and the time of breastfeeding initiation after delivery. Conclusion: children fell within normal limits for weight when breastfeeding duration was longer and vice versa. Regarding the undesirable effects(eg. malnutrition and obesity) of shortening the breastfeeding period on child health, provision of support as well as education about breastfeeding continuation is recommended